2022
DOI: 10.3390/metabo12050425
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Identifies a Novel Panel of Markers for Autologous Blood Transfusion

Abstract: Untargeted metabolomics was used to analyze serum and urine samples for biomarkers of autologous blood transfusion (ABT). Red blood cell concentrates from donated blood were stored for 35–36 days prior to reinfusion into the donors. Participants were sampled at different time points post-donation and up to 7 days post-transfusion. Metabolomic profiling was performed using ACQUITY ultra performance liquid chromatography (UPLC), Q-Exactive high resolution/accurate mass spectrometer interfaced with a heated elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…61 On the other hand, a second investigation reported 11 serum and 8 urinary metabolites altered at different time points after blood donation and up to 7 days post-reinfusion. 63 Although plasticizer markers tend to be rapidly eliminated, nine other serum and urine metabolites showed a detection window beyond 7 days, making their monitoring particularly promising for ABT screening. Therefore, based on these promising results, metabolomics will definitely be the field of forthcoming research in the near future, 137 although external influences can be sources of disturbances during a longitudinal follow-up (e.g., intense exercise or nutritional supplements).…”
Section: Metabolomic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…61 On the other hand, a second investigation reported 11 serum and 8 urinary metabolites altered at different time points after blood donation and up to 7 days post-reinfusion. 63 Although plasticizer markers tend to be rapidly eliminated, nine other serum and urine metabolites showed a detection window beyond 7 days, making their monitoring particularly promising for ABT screening. Therefore, based on these promising results, metabolomics will definitely be the field of forthcoming research in the near future, 137 although external influences can be sources of disturbances during a longitudinal follow-up (e.g., intense exercise or nutritional supplements).…”
Section: Metabolomic Analysesmentioning
confidence: 99%
“…Focusing on urine samples, a first study suggested several metabolites from plasticizers as the most relevant markers after blood reinfusion 61 . On the other hand, a second investigation reported 11 serum and 8 urinary metabolites altered at different time points after blood donation and up to 7 days post‐reinfusion 63 . Although plasticizer markers tend to be rapidly eliminated, nine other serum and urine metabolites showed a detection window beyond 7 days, making their monitoring particularly promising for ABT screening.…”
Section: Metabolomic Analysesmentioning
confidence: 99%
“…If transcriptomic and proteomic investigations have shown their interest ( 33 ), a metabolomic approach has recently demonstrated an interesting perspective ( 34 ). In this context, a recent study identified a panel of metabolites following autologous blood transfusion ( 35 ). Also applied for the screening of growth hormone ( 36 ) and testosterone misuse ( 37 ), individualized reference ranges seem to be the most promising approach ( 34 ).…”
Section: Investigation Of New Anti-doping Strategiesmentioning
confidence: 99%
“…115,116 Accordingly, it appears unlikely that other metabolites in urine are of interest for detection of ABT, although a small and uncontrolled study indicated that other urinary biomarkers could be of value. 117 However, metabolome changes within the plasma or RBC may prove valuable, especially as the total hemoglobin mass can remain elevated for more than 4 weeks following blood reinfusion, 118 indicating that the transfused cells are present for a long period of time.…”
Section: Omicsmentioning
confidence: 99%